2009
DOI: 10.3198/jpr2008.05.0272crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘CP 00‐2180’ Sugarcane

Abstract: ‘CP 00‐2180’ (Reg. No. CV‐134, PI 654093) sugarcane (a complex hybrid of Saccharum spp.) was developed through cooperative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugar Cane League, Inc., and was released to growers in Florida in September 2007. CP 00‐2180 was selected from a self‐cross of cultivar HoCP 91‐552 made at Canal Point, FL, in January 1998. Based on its high cane yields and fiber content (16%), HoCP 91‐552 was released as a cultivar for bioenergy in Louisiana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…The plot size is 4.6 m long and 3 m wide with 1.5 m of row spacing. All values of theoretical recoverable sucrose were multiplied by 0.86 to approximate CRS according to Glaz et al (2009) who reported this conversion factor based on a large number of samples from the Florida sugarcane industry and previous Canal Point research. These Stage II clones are evaluated for diseases in June through July of the coming year and for yield and final harvest in October through November on plant cane crop only in the CP program (Zhao et al, 2012b).…”
Section: Methodsmentioning
confidence: 99%
“…The plot size is 4.6 m long and 3 m wide with 1.5 m of row spacing. All values of theoretical recoverable sucrose were multiplied by 0.86 to approximate CRS according to Glaz et al (2009) who reported this conversion factor based on a large number of samples from the Florida sugarcane industry and previous Canal Point research. These Stage II clones are evaluated for diseases in June through July of the coming year and for yield and final harvest in October through November on plant cane crop only in the CP program (Zhao et al, 2012b).…”
Section: Methodsmentioning
confidence: 99%
“…These include Louisiana sugarcane cultivar Ho 95-988 [18], HoCP 96-540 [19], Ho 00-950 [20], HoCP 91-552 [21], and Ho 00-961 [22]. In addition, molecular descriptors were also included in sugarcane cultivar registration articles from the Florida sugarcane breeding program, including CPCL 97-2730 [23], CP 00-1101 [24], CP 88-1165 [25], CP 00-1446 [26], and CP 00-2180 [27]. All the molecular descriptors of newly released Louisiana sugarcane cultivars are produced from SSR DNA marker-based genotyping that are stored in the local molecular identity database.…”
Section: Discussionmentioning
confidence: 99%
“…Ten‐stalk samples were collected from the middle row of each plot between October and March in each crop‐year, weighed, and milled to derive CY, CRS, SY, and EI. The fiber content of CPCL 05‐1201 was determined as described by Glaz et al (2009).…”
Section: Methodsmentioning
confidence: 99%